PIERCE’S SEMIOTICS ANALYSIS ON BENNY’S CARTOONS RELATED TO COVID 19 ISSUES - Robingah, Robingah (Journal of Language and Literature, 2020)
This journal article focuses to analyze signs contained in Kartun Benny regarding to issues of coronavirus happened these days in Indonesia and many countries in the world. Kartun Benny is cartoon which is published in online portal media, Kontan.co.id. Kartun Benny is published regarding to the current issues happened in Indonesia. The aim is to find the meaning contained Kartun Benny regarding to the coronavirus issues. To analyze the cartoon, Pierce’s theory of semantic is used. From the three levels of trichotomy, only one level which is the second level is used to find the meanings. Qualitative method is used in conducting the research. After analyzing the meaning of the Kartun Benny on the 2 editions, which are 21st and 29th of March 2020, the result shows: Kartun Benny is categorized as humorous cartoon. The function of the release of this cartoon is to give sense of humor to the citizen, not to give critic or satire to the government, to picture the condition of how the people live in the situation of the spreading of coronavirus, and after knowing every policies and instruction given by the Government. In addition, Kartun Beny shows the condition and the respond of the society regarding the issues, the news, and the policies given by the government about the spreading of coronavirus.